Quality of Bronchial Biopsies for Morphology Study and Cell Sampling: A Comparison of Asthmatic and Healthy Subjects - Labonté, Isabelle; Laviolette, Michel; Olivenstein, Ron; Chakir, Jamila; Boulet, Louis-Philippe; Hamid, Qutayba (Canadian respiratory journal, 2008)
BACKGROUND: Bronchial biopsies are widely used for histopathological, primary cell culture and genetic studies, but very few reports have evaluated their quality. OBJECTIVES AND METHODS: The present project evaluated the quality (using a scoring system) and the general morphology of a pool of six bronchial biopsy specimens taken from three different sampling sites (the lobar, segmental and subsegmental carinae) in 27 subjects (13 asthmatic subjects and 14 healthy controls). The present study also assessed quantitative measurements of structural changes related to asthma. RESULTS: In total, 94.4% of the biopsy attempts had enough tissue to be processed. From these, 61.7% were scored with a good to excellent quality, while 76.5% presented smooth muscle bundles and 40.5% had an intact epithelium wall. The data also confirmed the structural changes observed in asthma, such as increased apparent thickening of the basement membrane, reduced amounts of smooth muscle for healthy controls and decreased percentage of intact epithelium for asthmatic subjects. CONCLUSION: A pool of six bronchial biopsy specimens can provide tissue of excellent quality in both asthmatic and healthy subjects and, consequently, a valuable sample for morphological analysis of mucosal structures.